2006
DOI: 10.1093/gerona/61.7.663
|View full text |Cite
|
Sign up to set email alerts
|

Atrogin-1/MAFbx and MuRF1 Are Downregulated in Aging-Related Loss of Skeletal Muscle

Abstract: Muscle atrophy in many conditions share a common mechanism in the upregulation of the muscle-specific ubiquitin E3-ligases atrophy gene-1/muscle atrophy F-box (Atrogin-1/MAFbx) and muscle ring-finger protein 1 (MuRF1). E3-ligases are part of the ubiquitin proteasome pathway utilized for protein degradation during muscle atrophy. In this study, we provide new data to show that this is not the case in age-related loss of muscle mass (sarcopenia). On the contrary, Atrogin-1/MAFbx and MuRF1 are downregulated in sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
121
3
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(139 citation statements)
references
References 73 publications
10
121
3
1
Order By: Relevance
“…52 These studies suggest that the association between Atrogin-1 and muscle atrophy may be fiber type-or gender-dependent. Another explanation could be that sarcopenia is mechanistically different from acute muscle atrophy, which is marked by increased expression of Atrogin-1, as suggested by Edstrom et al 51 This statement is supported by the findings of Giresi and colleagues, 45 who conducted a microarray study with muscle samples from 19-25-yr-old and 70-80-yr-old male subjects to identify the molecular signature of sarcopenia.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…52 These studies suggest that the association between Atrogin-1 and muscle atrophy may be fiber type-or gender-dependent. Another explanation could be that sarcopenia is mechanistically different from acute muscle atrophy, which is marked by increased expression of Atrogin-1, as suggested by Edstrom et al 51 This statement is supported by the findings of Giresi and colleagues, 45 who conducted a microarray study with muscle samples from 19-25-yr-old and 70-80-yr-old male subjects to identify the molecular signature of sarcopenia.…”
Section: Discussionmentioning
confidence: 71%
“…In experimental animal studies, Atrogin-1 has been shown to be highly expressed in skeletal muscles which were atrophying due to fasting or diverse diseases. 36,37 In very recent studies, downregulation of ATROGIN-1 in sarcopenic, slow-twitch muscles of aged, female rats was demonstrated 51 whereas opposite results were obtained in fasttwitch muscles of aged, male rats. 52 These studies suggest that the association between Atrogin-1 and muscle atrophy may be fiber type-or gender-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the aged muscles, mRNAs for Atrogin-1/MAFbx, MuRF1, and the Ub-conjugating enzyme, E2-14K, were unchanged or lower than adult levels (Fig. 7A) (36). Also, treatment with the glucocorticoid, dexamethasone (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, it has been shown that atrogin-1/MAFbx and MuRF1 are down-regulated as a result of AKT (protein kinase B)-mediated inactivation of Foxo4. This activation of AKT was shown to be mediated through the insulin-like growth factor-1 (IGF-1) receptor signalling [14]. Finally, it has been shown that activation of AMPK stimulates myofibrillar protein degradation through the expression of atrogin-1/MAFbx and MuRF1 by increasing Foxo transcription factors in skeletal muscles [15].…”
Section: Discussionmentioning
confidence: 99%
“…AMPK has been shown to enhance muscle protein degradation through promoting the expression of two muscle-specific ubiquitin ligases, MAFbx and MuRF1 [17]. Muscle atrophy in many conditions share a common mechanism in the up-regulation of MAFbx and MuRF1, both of which are part of the ubiquitin proteasome pathway utilized for protein degradation during muscle atrophy [14].…”
Section: Discussionmentioning
confidence: 99%